Expression of Symbols Related to Idea of Fetishism in the Territory of Uzbekistan (Global Journal of Human-Social Science, 2022)
This article analyzes the representation of symbols related to the ideas of fetishism in the territory of Uzbekistan It discusses the symbols and symbols of the ancient pre-Islamic and post-Islamic religious beliefs of the ancient peoples and nations that historically existed in the territory of Uzbekistan Examples from ancient sources are given in a new interpretation
Keywords: fetishism; symbol; emblem; attribute inverted interpretation; idol; god; deity and gods